Wettability of nanofluid-modified oil-wet calcite at reservoir conditions - Al-Anssari, S.; Arif, M.; Wang, Shaobin; Barifcani, Ahmed; Lebedev, M.; Iglauer, Stefan (Elsevier Ltd, 2018)
© 2017 Elsevier Ltd Nanofluids, liquid suspensions of nanoparticles (Np), are an effective agent to alter the wettability of oil-wet reservoirs to water-wet thus promoting hydrocarbon recovery. It can also have an application to more efficient carbon storage. We present a series of contact angle (?) investigations on initially oil-wet calcite surfaces to quantify the performance of hydrophilic silica nanoparticles for wettability alteration. These tests are conducted at typical in-situ high pressure (CO 2 ), temperature and salinity conditions. A high pressure–temperature (P/T) optical cell with a regulated tilted surface was used to measure the advancing and receding contact angles at the desired conditions. The results showed that silica nanofluids can alter the wettability of oil-wet calcite to strongly water-wet at all operational conditions. Although limited desorption of silica nanoparticles occurred after exposure to high pressure (20 MPa), nanoparticle adsorption on the oil-wet calcite surface was mainly irreversible. The nanofluid concentration and immersion time played crucial roles in improving the efficiency of diluted nanofluids while salinity was less significant at high pressure and temperature. The findings provide new insights into the potential for nanofluids being applied for improved enhanced oil recovery and carbon sequestration and storage.